Case reportA case report of ultrasound-guided interstitial brachytherapy for abdominal wall metastases of ovarian cancer - Shi, Dan; Wu, Ning; Zhao, Hongfu; He, Mingyuan; Han, Dongmei; Cheng, Guanghui (Journal of Contemporary Brachytherapy, 2015)
Purpose: To report the treatment effect of interstitial brachytherapy for abdominal wall metastases of ovarian cancer. Material and methods: The patient is a 44-year-old female with a diagnosis of stage IA ovarian cancer. After surgery and two cycles of chemotherapy with paclitaxel and carboplatin, the patient noticed dull pain in the lower abdomen and found a mass located in the subcutaneous tissue, below the operative incision. A diagnostic biopsy showed abdominal wall metastases. After external radiotherapy with a dose of 39.6 Gy in 22 fractions, the residual tumor was treated with interstitial brachytherapy under ultrasound guidance. The brachytherapy dose was 18 Gy in 6 fractions of 3 Gy each. Results: After 3 weeks of brachytherapy, the tumor had disappeared completely. Interstitial brachytherapy was feasible. Conclusions : Interstitial brachytherapy may be a proposed treatment strategy for inoperable superficial metastases, especially for low radiosensitivity cancer.